Islamic Law: An Introduction - Mohamad Akram Laldin (International Islamic University Malaysia, 2006)
This work is an attempt to provide some light into the basic principles of Islamic law in order to understand the purpose of the revelation of rulings in Islam. This understanding is very importatnt to be understood particularly by students and researchers in the field of Islamic law. This book also examines five important legal maxims.